THE IMPLEMENTATION OF SCIENTIFIC LEARNING APPROACH AT 10th GRADE ENGLISH CLASSES OF SENIOR HIGH SCHOOL 4 KOTA BENGKULU - Hikma Wipaqi (JOALL (Journal of Applied Linguistics and Literature), 2017)
The purpose of this research is to determine the application of the scientific approach in teaching of English for 10th grade at Senior High School 4 Bengkulu City. This research used the descriptive method. The subject of this research was the English teacher at Senior High School 4 Kota Bengkulu. The number of participants in this research were 3 English teachers who tough in 10th grade. This study used observation checklist as an instrument. Observation checklist consisted of three main components. The first component consisted of five phases of scientific approach. They were observing, asking, exploring, associating and communicating. The second component was learning materials that supported the implementation of scientific learning approach and the third component was an assessment in scientific learning approach. The results of this study indicated that the implementation of scientific learning approach included the all five phases reached an average of 3.13 ( in ‘good ‘category),  observing phase reached an average 2.80 ( in ‘fair” category),  asking phase reached an average of 3.15 ( in ‘good; category), exploring phase  reached an average of 3.18 ( in’ good ‘category), phase associating reached an average of 3.47 ( in ‘very good’ category)  and  communicating phase reached an average of 3.06 (in’ good ‘category). The second component of development of the material reached an average of 3.72 ( in’ very good’ categories) and the third component was an assessment reached 3.67 (in ‘very good’ category).